Simultaneous utilization of CO2 and potassium-rich biomass for the environmentally friendly production of potassium formate - Yoon, Hayoung; Park, Kwangho; Jung, Kwang-Deog; Yoon, Sungho (Royal Society of Chemistry, 2025)
The C1 chemical species, potassium formate (K(HCO2)), known as a two-electron reducing agent, finds application in the synthesis of multi-carbon compounds, including oxalate, and plays a crucial role not only in the food and pharmaceutical industries but also across various sectors. However, the direct hydrogenation of CO2 to produce K(HCO2) remains a challenge. Addressing this issue, efficient production of K(HCO2) is achieved by integrating CO2 hydrogenation in a trickle-bed reactor using a heterogeneous catalyst with a novel separation method that utilizes potassium ions from biomass ash for formic acid derivative product isolation. Through alkaline-mediated CO2 hydrogenation using N-methylpyrrolidine (NMPI), a concentrated 5 M NMPI solution of formic acid N-methylpyrrolidine complex ([NMPIH][HCO2]) was formed, facilitating the synthesis of K(HCO2) with over 99% purity via reaction with excess K ions contained within Bamboo ash. Notably, 80% of CO2 was converted to formate ions, and NMPI was expected to be effectively recycled as it was completely removed during the evaporation process for K(HCO2) separation. Additionally, this process yielded SiO2 by-product particles with sizes ranging from 10 to 20 nm. This research highlights a novel strategy contributing to sustainable environmental management and resource recycling by effectively utilizing CO2 as a valuable feedstock while concurrently producing valuable chemical compounds from waste materials.